Le culte de Maxime de Riez : premiers jalons (I) - Thierry Pécout (Bulletin du Centre d’Études Médiévales d’Auxerre)
Maxime was bishop of Riez (Alpes-de-Haute-Provence) after having been abbot of Lérins. His worship spread immediately after his death at the end of the 5th century. The exemple of Maxime illustrates the plasticity of the cult of a monk and bishop based on an ancient collection of hagiographical works. Worship is attached to a local diocesan identity but soon merges with a classic set of prestigious models that widely circulate through collections of saints’lives and martyrologies. Maxime has been the object of various appropriations, especially in Flanders, in the Viennois, and in northern Italy, the sources of which are examined here. The hagiographic file of Maxime needs a reconstitution and a rereading on various levels.